2018
DOI: 10.1038/s41598-018-21296-y
|View full text |Cite
|
Sign up to set email alerts
|

Species-specified VOC emissions derived from a gridded study in the Pearl River Delta, China

Abstract: This study provides a top-down approach to establish an emission inventory of volatile organic compounds (VOC) based on ambient measurements, by combining the box model and positive matrix factorization (PMF) model. Species-specified VOC emissions, source contributions, and spatial distributions are determined based on regional-scale gridded measurements between September 2008 to December 2009 in the Pearl River Delta (PRD), China. The most prevalent anthropogenic species in the PRD was toluene estimated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Vehicle exhaust sources are characterized by high concentrations of alkanes (Cai et al, 2010), a few alkenes (An et al, 2017;Liu et al, 2008a), acetylene (Ling et al, 2011), and C6-C7 aromatics (Mo et al, 2018). In this study, vehicle exhaust sources in the CB and QL sites exhibited high ethane, propane, butane, and acetone contents.…”
Section: Sources Apportionmentmentioning
confidence: 65%
“…Vehicle exhaust sources are characterized by high concentrations of alkanes (Cai et al, 2010), a few alkenes (An et al, 2017;Liu et al, 2008a), acetylene (Ling et al, 2011), and C6-C7 aromatics (Mo et al, 2018). In this study, vehicle exhaust sources in the CB and QL sites exhibited high ethane, propane, butane, and acetone contents.…”
Section: Sources Apportionmentmentioning
confidence: 65%
“…In paint solvent usage source emission studies, the ratio of T / B was greater than 8.8 ± 6.5 by different solvent use process (Yuan et al, 2010;Wang et al, 2014;Zheng et al, 2013). In burning source emission studies, the T / B ratio was approximately 0.3 ± 0.1 in different combustion process and raw materials (Liu et al, 2008a;Li et al, 2011;Mo et al, 2016). In order to reduce the influence of photochemical reaction on the ratio of benzene to toluene, this study selected the weaker photochemical reaction period (03:00-07:00) for the analysis of toluene and benzene (Fig.…”
Section: Specific Voc Ratiosmentioning
confidence: 96%
“…In industrial source emission studies, the ratio of T / B ranged from 1.4 ± 0.8 to 5.8 ± 3.4 by different industry type and process unit (Mo et al, 2015;Shi et al, 2015). In traffic source emission studies, the ratio of T / B ranged from 0.9 ± 0.6 to 2.2 ± 0.5 by different vehicle type and fuel composition (Qiao et al, 2012;Dai et al, 2013;Wang et al, 2013;Yao et al, 2013;Zhang et al, 2013; Mo et al, 2016;Yao et al, 2015a;Deng et al, 2018). However, vehicle emissions include both diesel vehicles emissions and gasoline vehicles emissions in the atmospheric environment.…”
Section: Specific Voc Ratiosmentioning
confidence: 99%
“…The emissions of anthropogenic VOCs, the key precursors of ambient O 3 and PM 2.5 , have doubled during the past two decades (Zhao et al, 2017). Previous studies have been conducted to analyze the characteristics and identify the sources of ambient VOCs using receptor models on megalopolis clusters such as the Beijing-Tianjin-Hebei (BTH) region (Li et al, 2015;, the Yangtze River Delta (YRD) region (Mo et al, 2017;Zhu et al, 2018) and the Pearl River Delta (PRD) region (Zhang et al, 2015;Mo et al, 2018;Ou et al, 2018) in China. For example, An et al (2014) used principal component analysis/absolute principal component scores (PCA/APCS) to investigate VOCs sources at an industrial site in Nanjing.…”
Section: Introductionmentioning
confidence: 99%
“…However, the variation in the VOCs sources might be different for suburban areas. In the PRD region, for example, gridded measurements of VOCs were conducted, and spatial discrepancies in VOCs sources were observed (Mo et al, 2018;Ou et al, 2018). A larger contribution of industrial processes was found in the industrial area, while a larger contribution of gasoline-related sources was found in suburban zones.…”
Section: Introductionmentioning
confidence: 99%